Optimizing Career Woman's Financial Management Through Monthly Budget and Fintech: Optimalisasi Manajemen Keuangan Wanita Karier Melalui Anggaran Bulanan dan Fintech - Hasanah, Uswatun; Rahayu , Ruci Arizanda (Indonesian Journal of Law and Economics Review, 2024)
General Background: The financial management landscape for career women has evolved significantly in the digital era, particularly with the rise of financial technology (fintech). Specific Background: The integration of fintech facilitates budgeting and expense tracking, allowing career women to manage their finances more effectively. However, while fintech offers convenience, it may also contribute to impulsive spending behavior due to easy access to funds. Knowledge Gap: Existing literature lacks a comprehensive understanding of how career women utilize fintech for financial management and the implications of this technology on their budgeting practices. Aims: This study aims to explore the financial management strategies employed by career women in the digital era, focusing on budgeting, the application of accounting in household finances, and the impacts of fintech on their financial behaviors. Results: Career women effectively manage their finances through monthly budgets, reducing stress and achieving financial goals, but the convenience of fintech can increase wasteful expenditure. Novelty: This research contributes new insights into the intersection of career women's financial management, accounting practices, and fintech, addressing a critical gap in the literature. Implications: The study emphasizes the need for financial education for career women, emphasizing balanced practices to maximize fintech benefits and reduce impulsive spending, promoting financial stability and empowerment. Highlights: Budgeting aids career women in spending control and goal achievement. Fintech simplifies transactions, improving financial management efficiency. Ease of use may lead to impulsive spending behavior. Keywords: financial management, career women, fintech, budgeting, digital era